Litteratur. - Johs. Andenæs; A. Haslund; Karl O. Christiansen; Jon Johnsen; Jørgen Smith; Stephan Hurwitz; Knud Waaben; Franz Marcus; Carl Aude-Hansen; Nils Christie (Nordisk Tidsskrift for Kriminalvidenskab)
Intet resumé